Dark Photons and Their Correlation with The Dark Sector ‎Gravitons and The Higgs Boson H→γγ Decay - Markoulakis, Emmanouil; Valamontes, Antonios (International Journal of Physical Research, 2025)
In this paper, we present an in-depth phenomenological and technical description of the ATLAS LHC experiment, focusing on two-γ-photon decay events of the Higgs boson. We explore the implications of these decay events in the context of our novel theory, the ‎Superluminal Graviton Condensate Vacuum (SGCV). This theory predicts the existence of "superluminal propagating massless ‎dark photons”, which act as ghost particles of superluminal displaced vacuum dark sector gravitons. The detection of these particles ‎would establish a significant link between the Higgs field, the quantum field of normal photons, and the dark sector. We propose ‎experimental setups and Time-of-Flight (ToF) instrumentation detectors to validate these predictions, emphasizing their importance ‎for understanding the vacuum and the fabric of spacetime, which is hypothesized to be fundamentally composed of superluminal ‎vibration energy‎.